The Use of Soluble Silicon via Fertigation and Leaf Application in Panicum Maximum Modulates Production Without Decreasing Grass Quality - Buchelt, Antonio Carlos; de Mello Prado, Renato [UNESP]; Caione, Gustavo; de Moura Zanine, Anderson; Justina, Sabrina Machado Dela; da Silva Ribeiro, Jhonatas; de Souza Júnior, Antonio Martins; de Jesus Ferreira, Daniele; da Silva de Sousa, Francisca Claudia (Springer Nature, 2023)
Silicon is a beneficial element for forage grasses. However, to recommend its use, it is important to understand better whether it is possible to reconcile the increase in biomass production and no decreases in its quality. Because this information is lacking, this research aims to evaluate the effects of Si concentrations applied via fertigation with and without complement of Si leaf application on the agronomic characteristics, biomass production, and chemical composition of the grass Panicum maximum BRS cv. Zuri. The experiment was carried out in a greenhouse. The experiment had a 4 × 2 factorial design, being four concentrations of Si (0, 1.5, 3, and 4.5 mmol L−1) in the form of potassium silicate applied via fertigation in the absence and in the presence of a complementary application of Si via leaf (1.0 g L−1). This research shows that the use of high-soluble silicon at a concentration of 3.0 mmol L−1 via fertigation is sufficient to obtain an optimal nutritional efficiency and grass growth, with no need for complementary application of Si via leaf application. It is possible and viable to use Si for grasses, as it enhances the production of biomass without impairing the nutritional value and quality of the grass.
Keywords: Biomass; Forage grasses; Nutritional; Potassium silicate